Law after the welfare state: formalism, functionalism and the ironic turn of reflexive law - Peer Zumbansen (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2009)
This paper analyzes the contemporary emergence of neo-formalist and neo-functionalist approaches to law-making at a time when the state is seeking to reassert, reformulate and reconceptualize its regulatory competence, both domestically and transnationally. While the earlier turn to alternative regulation modes, conceptualized under the heading of 'legal pluralism,' 'responsive law,' or 'reflexive law' in the 1970s and 1980s, had aimed at a more socially responsive, contextualized, and ultimately learning mode of legal intervention, the contemporary revival of functionalist jurisprudence and its reliance on 'social norms' embraces a limitation model of legal regulation. After revisiting the Legal Realist critique of Formalism and the formulation of functionalist regulation as a progressive agenda, this paper reflects on both the American and German justifications of market regulation and the Welfare State in order to trace the different evolution towards 'responsive law' and legal pluralism in the U.S. and 'post-interventionist' and 'reflexive' law in Germany. This comparison allows for an identification of the emerging transnational qualities of legal normativity in the face of a declining welfare state paradigm, which - at the beginning of the 21st century - appears to provide the stage for turning the progressive gains of the former era into a set of market-oriented justifications of private autonomy and de-regulation. - Der Aufsatz rekonstruiert die wechselhafte Geschichte des Rechts nach dem Wohlfahrtsstaat'. Nachdem die Krise des Wohlfahrtsstaats in den 1970er Jahren vornehmlich als eine Frage der Regulierungs- und Steuerungskrise wahrgenommen wurde, traten 'responsive' und 'reflexive' Rechtstheorien gleichzeitig als Erben und Zerstörer des Rechts als Steuerungsmittel auf. Die Suche nach 'Alternativen zum Recht' in den USA wie auch in Deutschland mündete aber schon bald in eine weitreichende Privatisierungs- und Deregulierungsbewegung. Die sich schon lange ankündigende Skepsis nicht nur gegenüber parlamentarischer Gesetzgebung, sondern auch gerichtlicher Rechts(fort)bildung im Namen der Selbstregulierungskräfte der 'Privatrechtsgesellschaft' durch den Markt und 'social norms' verstärkte diese Kritik am Staat diesseits und jenseits des Atlantik. Der Aufsatz geht vor diesem Hintergrund der Frage nach, inwiefern die gegenwärtige Betonung gesellschaftlicher Selbstregulierung die Kritik der Rechtsrealisten und der frühen Rechtssoziologie am Rechtsformalismus aufgreift, nur um sie im Namen von Marktfreiheiten zu verkürzen und ihres kritischen Potentials beraubt.
Keywords: 330; Sozialstaat; Sozialrecht; Rechtsreform; Privatisierung; Deregulierung; Selbstverpflichtung; Kritik; USA; Deutschland